Feasibility of Home-Based Early Infant Hybrid Therapy in Children with Unilateral Cerebral Palsy - Palomo‐Carrión, Rocío; Romay Barrero, Helena Maria; Pinero‐Pinto, Elena; Romero-Galisteo, Rita Pilar; Coello-Villalón, María; Ferri-Morales, Asunción; López-Muñoz, Purificación; Lirio-Romero, Cristina (MDPI, 2024)
The first stage of childhood is characterized by great neuronal plasticity. In Unilateral Cerebral Palsy (UCP), it is essential to carry out early treatment, with family involvement. The aim of this study was to investigate the feasibility of Early Infant Hybrid Therapy (eI-Hybrid) applied at home with family involvement in children with UCP aged 9–18 months, and to assess its preliminary effectiveness on bimanual functional performance. Methods: A single group of 10 children (12.8 months, SD = 3.4) performed the eI-Hybrid therapy. The main outcome was measured with the mini Assisting Hand Assessment scale (mini-AHA), functional goals were measured with the Goal Attainment Scale (GAS), and satisfaction expectations on intensive therapy were also recorded. Three measures were performed (week 0, week 10, and month 6). A repeated-measures ANOVA test was performed on the mini-AHA in order to observe the statistically significant differences in pairwise comparison. Results: Ten children completed the study and the parents’ expectations were fulfilled, indicating high caregiver compliance and high adherence to the treatment. Clinically relevant changes were observed between pre- and post-intervention measurements in BFP (pre: 41.9 (SD: 7.7), post: 50.9 (SD: 6.0) and in the follow-up at 6 months (50.3 (SD:5.6); p < 0.001). Families reported a high satisfaction. Conclusions: infant hybrid treatment is feasible to be performed at home with the family’s involvement, obtaining improvements in the affected upper limb for early-age UCP
Keywords: Niños paralíticos cerebrales - Ejercicios terapéuticos; Neuroplasticidad; Early age; Family; Home; Infantile hemiplegia; Intensive therapy; Upper extremity